TINGKAT KEPUASAN PASIEN TERHADAP WEBSITE PENDAFTARAN ONLINE RAWAT JALAN MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) DI RSUD SINGAPARNA MEDIKA CITRAUTAMA (SMC) - Muslimah, Septi Jamiatul; Kurniasih, Dewi Lena Suryani; Triyanti, Endang; Lutfi, Epi Edward (Jurnal Informasi Kesehatan Indonesia (JIKI), 2023)
Background: The government is currently creating an innovative system, called the online registration system, in tandem with the advancement of information technology, this system aims to make patient registration easier and reduce on the length of time people must wait in line to get the a queue number. The implementation of online registration at the Singaparna Medika Citrautama (SMC) Hospital still has problems, such as running into errors, for patients to be satisfied with online registration, it must comply with particular standards, considering that patient satisfaction is an indicator of the quality of health services. With using the End User Computing Satisfaction (EUCS) method at Singaparna Medika Citrautama (SMC) Hospital, this research aims to determine the level of patient satisfaction with the outpatient online registration website.Subjects and Method: This study uses a type of quantitative research with a descriptive approach. With 97 patients as the sample, incidental sampling was used to select the sample. use a questionnaire sheet to retrieve data. Univariate data analysis is used in the analysis.Results: Based on research result, the levels of satisfaction based on the content dimension are very satisfied by 18.6% and 74.2% satisfied, the accuracy dimensions are very satisfied by 27.8% and 58.8% satisfied, the format dimensions are very satisfied by 18.6% and 72.2% satisfied, the ease of use dimensions are very satisfied by 29.9% and 66% satisfied, and the timeliness dimensions are very satisfied by 20.6% and 76.3% satisfied.Conclusion: Although there are still problems with its use, including the occurrence of errors, patient satisfaction with the online registration website shows good results.